The Memory of the Stones - Holy Places in Early Medieval Croatia - Jurković, Miljenko (1996)
The topic of the round table is discussed from sociological, philosophical, cultural and historical point of view. The author tries to picture holy places on well documented material - monuments of Early Medieval Croatian state - on both points of view: from today's historical panorama as well as from the historical conspectus of the time to which they belong.
Projekt MZOS
ENG